Partnering with athletes to assess risk of COVID-related myocarditis - Kay, B. W.; Feher, A.; Reinhardt, S.; Cuomo, J.; Arlis-Mayor, S.; Lynch, M.; Johnson, K.; Kemp, P.; Wagner, H.; Welsh, T.; Lamy, J.; Peters, D.; et al. (MedRxiv The preprint server for health sciences, 2022)
Background: Myocarditis in athletes is a feared complication of SARS-CoV-2, yet guidelines for screening with cardiac magnetic resonance imaging are lacking. Further, stakeholder involvement in the research is rare. Hypothesis: We sought to determine the rates of cardiac magnetic resonance imaging evidence of SARS-CoV-2 related myocarditis in student athletes. We hypothesized that rates of myocarditis were lower than initially reported and that including athletes on the research team would enhance participant satisfaction and scientific integrity. Methods: Accordingly, when members of a hockey team were infected with SARS-CoV-2, we invited them and their team physicians to be part of the design of a study assessing the incidence of myocarditis. We performed cardiac magnetic resonance imaging on participating hockey players infected with SARS-CoV-2 and compared them to a healthy lacrosse cohort. Participants were given an optional survey to complete at the end of the study to assess their satisfaction with it. Results: Four hockey players and two team physicians joined the study team; eight hockey players and four lacrosse players participated in the study. Zero athletes met imaging criteria for myocarditis; delayed enhancement was observed in seven cases and three controls. Athletes supported sharing the findings with the participants. No athletes reported feeling uncomfortable participating, knowing other athletes participated on the research team. Conclusion: Rates of SARS-CoV-2 myocarditis in young athletes appears to be lower than initially reported. Partnered research is important, especially in populations with more to lose, such as collegiate athletes; future studies should include stakeholders in the study design and execution. Key points: Cardiac MRI findings of myocarditis after COVID infection in young athletes is rare. Subjects of research studies appreciate involvement in the development of the study, and this also builds trust with the research team.